Molecular typing of T. pallidum clinical isolates and their resistance to macrolides in the Russian Federation during 2018-2019 - V. S. Solomka; T. M. Komyagina; A. V. Chestkov; A. P. Obukhov; D. G. Deryabin (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Based on arp, tprII and tp0548 genes variability molecular typing of Treponema pallidum is a worldwide method for syphilis epidemiology analysis, including the ability to monitor antimicrobial-resistant variants of the causative agents of the disease.The aim of the study is to characterize the molecular subtypes of T. pallidum isolated from syphilis patients' clinical material in 2018-2019, to assess the known antibiotic resistance determinants presence, and to compare the results with known Russian and foreign data.Materials and methods. 64 T. pallidum clinical isolates obtained from 10 regions of the Russian Federation: Astrakhan, Irkutsk, Kaluga, Moscow, Novosibirsk and Omsk regions, the Stavropol Territory, the Republic of Sakha (Yakutia), Tuva and Chuvashia were studied. The arp gene variability was estimated by the number of internal tandem repeats from 60 base pairs analyzed by PCR. The variability of tprII genes was based on the restriction fragment length polymorphism. The nucleotide sequence of the tp0548 gene with a length of 84 base pairs (positions 131-215) variable region, as well as the genetic determinants of macrolide resistance in the 23S rRNA gene, were studied by capillary sequencing.Results. 14 d/f molecular subtype of T. pallidum was absolutely prevalent in 9 of 10 examined subjects of the Russian Federation, taking 93.75 % of the total number of clinical isolates, and it was consistent with data on its stable dominance over 2011-2017. The most common in Western Europe molecular  subtype of T. pallidum 14 d/g was found in the Kaluga and Omsk regions, taking 4.69 % of the analyzed samples. The molecular subtype of T. pallidum 14 b/f, sporadically but stably occurring over the many years of monitoring, was represented by a single clinical isolate (1.56 %) from the Republic of Tuva. A2058G 23S rRNA mutation causing resistance to macrolides was detected both in all (3 of 3) representatives molecular subtype 14 d/g and in 2 of 60 clinical isolates molecular subtype 14 d/f (from Moscow and Omsk region). In fact, the resistance to macrolides was found in 7.81 % T. pallidum Russian clinical isolates found during 2018-2019, that exceeds the WHO threshold level allowing to recommend a drug for the STI treatment.Conclusion. The contemporary molecular epidemiology of syphilis in the Russian Federation is characterized by the dominance of the molecular subtype T. pallidum 14 d/f, and significantly distinguishes the local population from those in the neighboring states of Europe and Asia. The continued spread of the determinants of resistance to macrolides makes us cautious about the use of this group of drugs for the treatment of syphilis and is an argument in favor of an appropriate review of current clinical recommendations.